Revisando la ecuación de van der Waals - Bonilla, B.; Herrera, J.N. (Revista Mexicana de Física E, 2006)
From the results of the classic statistical mechanics we can deduce, over a formal way, the van der Waals (vdW) equation, using like model interaction potential an square well, also we show that the perturbation theory can be used to deduce the same result, but with a variant, the potential model used is proportional to an interaction 1/r^s, where s>3, and r is the relative distance. With this, one demonstrates that formally the vdW equation is one first correction to the ideal gas equation. We obtain all the van der Waals`s thermodynamic properties and the coexistence curve. We used to construct the vdW coexistence curve by different methods, by a graphical method, a numerical and an analytical one.